2022
DOI: 10.1007/s11356-022-23347-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on the potential risks under a hazardous gas leakage accident: effects of source characteristics and ambient wind velocities

Abstract: In this study, a full scale storage tank was established to investigate the potential risks of leakage accident. We have developed a series of leak scenarios that close to real accidents, and have divided the ambient areas according to relevant regulations. Considering the variety and complexity of real-life accident scenarios, the presented work revealed the combined effect of source release intensity and ambient wind speed on dispersion features by classifying leakage scenarios into active or passive release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The faster the diffusion speed, the longer the diffusion distance, and the larger the diffusion area. Liu 15 found through full-size experiments that the leakage on the windward side is the most dangerous release mode when the approaching wind speed is low; with the increase of the wind speed, the jet angle perpendicular to the incoming wind produces the largest cloud. Pei 16 performed a diffusion modeling of chlorine leakage based on the Fluent software, and found that in the case of the wind speed of 10 m/s, the molar concentration of chlorine gas at the monitoring point downwind of the building first increased and then decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The faster the diffusion speed, the longer the diffusion distance, and the larger the diffusion area. Liu 15 found through full-size experiments that the leakage on the windward side is the most dangerous release mode when the approaching wind speed is low; with the increase of the wind speed, the jet angle perpendicular to the incoming wind produces the largest cloud. Pei 16 performed a diffusion modeling of chlorine leakage based on the Fluent software, and found that in the case of the wind speed of 10 m/s, the molar concentration of chlorine gas at the monitoring point downwind of the building first increased and then decreased.…”
Section: Introductionmentioning
confidence: 99%